2012
DOI: 10.1002/adfm.201202190
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Concentration Mapping of Organic Blends

Abstract: The three‐dimensional morphology of mixed organic layers are quantitatively measured using high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) with electron tomography for the first time. The mixed organic layers used for organic photovoltaic applications have not been previously imaged using STEM tomography as there is insufficient contrast between donor and acceptor components. Contrast is generated by substituting fullerenes with endohedral fullerenes that contain a Lu3N clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 55 publications
3
100
1
Order By: Relevance
“…Concentration-specific 3D morphology of a BHJ film measured using HAADF-ET. 62 Assignment of photovoltage features F1−5 is shown with respect to the location within the films. HAADF-ET does obtain contrast from density changes only, so no assignment of crystallinity is made here.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration-specific 3D morphology of a BHJ film measured using HAADF-ET. 62 Assignment of photovoltage features F1−5 is shown with respect to the location within the films. HAADF-ET does obtain contrast from density changes only, so no assignment of crystallinity is made here.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 5 maps the observed SPV features to distinct spatial regions in the polymer film. According to electron tomography data, 62,63 thermally annealed BHJ films contain three different phases, a fullerene-rich amorphous phase (∼10% P3HT by volume), a P3HT−fullerene mixed amorphous phase, and pure P3HT domains. The substrate surface has a higher density of the fullerene-rich and mixed phases, while the pure-P3HT domains are near the center of the film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The layer formed at 180 C shows higher series resistance at higher forward potentials demonstrating that the number of doped paths through the P3HT/PSS interlayer is lower than for the interlayer annealed at 210 C. A normal annealed BHJ device will have some doped P3HT mixed with PSS, but vertical concentration measurements have shown that in fact, crystalline domains do not extend to the PEDOT:PSS interface and the PCBM concentration at the interface is still near 50%. [61][62][63][64] This comparison shows that P3HT/PCBM BHJ mixtures have high PCE under a variety of morphological conditions.…”
Section: Interlayers In Devicesmentioning
confidence: 99%
“…P3HT is a semicrystalline polymer and the crystalline domains at immiscible with PCBM while the amorphous domains mix with PCBM. So the mixed morphology is either two or three phased depending on whether there is enough PCBM to fill the amorphous P3HT volume [26,80,81]. The cited DPD model generates a two phase morphology at all mixing ratios and thus produces morphologies that are bi-continuous but not physically relevant to P3HT.…”
Section: Chemistry Vs Morphologymentioning
confidence: 99%
“…Neutron scattering methods measure the structure and dynamics of hydrogen atoms in organic electronics through coherent scattering (small angle neutron scattering) and/or energy loss measurement (inelastic neutron scattering) [24]. Electron microscopy and tomography create 2D and 3D images of OPV device layers with nanometer resolution [25,26]. Similar to neutron methods, electromagnetic radiation techniques study both the structure and dynamics of non-hydrogen atoms in organic electronics, as the atomic electromagnetic cross-section increases with atomic number.…”
Section: Contact Roland Faller Rfaller@ucdavisedumentioning
confidence: 99%